TA'LIM AL-QAWA'ID AL-NAHWIYAH 'ALA ASAS MADKHAL AL-TANWIM AL-MAGHNATHISI - Danial Hilmi (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
Teaching of Arabic grammar in university needs to innovation in building teaching and learning methods that meet students' brain needs. However, the problem of teaching basic grammar lies in their lack of understanding in building what they have learned. To solve this problem, the author introduces grammar instruction on the basis of the hypnosis entrance that invites them to learn to introduce encouraging words in the subconscious mind so as to add enthusiasm to the desired achievement as desired. In education, it is an important element to invite students to focus on the use of the learned material. The result indicates that the entrance to hypnosis is effective to solve problems of grammatical rules in university education.